Superstar Returns? Spatial Heterogeneity in Returns to Housing - AMARAL, FRANCISCO; DOHMEN, MARTIN; KOHL, SEBASTIAN; SCHULARICK, MORITZ (Journal of Finance, 2025)
ABSTRACT This paper makes the first comprehensive attempt to study within‐country heterogeneity of housing returns. We introduce a new city‐level data set covering 15 OECD countries over 150 years and show that national housing markets are characterized by systematic spatial variation in housing returns. Total returns in large agglomerations are close to 100 basis points lower per year than in other parts of the same country. Excess returns outside the large cities can be rationalized as compensation for higher risk, especially higher covariance with income growth and lower liquidity. Real estate in diversified large agglomerations is comparatively safe.